Safety and efficacy of tofacitinib for treatment of ulcerative colitis: final analysis of OCTAVE Open, an open‐label, long‐term extension study with up to 7.0 years of treatment. Issue 4 (1st December 2021) - Sandborn, William J.; Lawendy, Nervin; Danese, Silvio; Su, Chinyu; Loftus, Edward V.; Hart, Ailsa; Dotan, Iris; Damião, Adérson O. M. C.; Judd, Donna T.; Guo, Xiang; Modesto, Irene; Wang, Wenjin; et al.
Summary: Background: Tofacitinib is an oral, small molecule Janus kinase inhibitor for the treatment of ulcerative colitis. We present final data from OCTAVE Open, an open‐label, long‐term extension study. Aims: The primary objective of OCTAVE Open was to assess the safety and tolerability of long‐term tofacitinib in patients with ulcerative colitis; evaluating efficacy was a secondary objective. Methods: Eligible patients included OCTAVE Induction 1&2 non‐responders and OCTAVE Sustain completers/treatment failures. Patients in remission at OCTAVE Open baseline received tofacitinib 5 mg b.d.; all others received 10 mg b.d. Incidence rates (unique patients with events/100 patient‐years) for adverse events of special interest were calculated; ≤7.0 years of observation. Efficacy endpoints derived from Mayo score were reported ≤36 months (last scheduled endoscopy visit). Results: In OCTAVE Open, 769 of 944 patients (81.5%) initially received tofacitinib 10 mg b.d. Among all patients (2440.8 patient‐years of exposure), incidence rates (IRs; 95% confidence intervals) for deaths and adverse events of special interest were: deaths, 0.25 (0.09‐0.54); serious infections, 1.61 (1.14‐2.20); herpes zoster (non‐serious and serious), 3.16 (2.47‐3.97); opportunistic infections, 0.87 (0.54‐1.33); major adverse cardiovascular events, 0.16 (0.04‐0.42); malignancies (excluding non‐melanoma skin cancer), 1.03 (0.67‐1.52); non‐melanoma skin cancer, 0.75 (0.45‐1.19); deep vein thrombosis, 0.04 (0.00‐0.23); pulmonary embolism, 0.21 (0.07‐0.48). At Month 36, 66.9% and 40.3% showed clinical response, 64.6% and 37.1% had endoscopic improvement, and 58.9% and 33.7% maintained or achieved remission, with tofacitinib 5 and 10 mg b.d. respectively. Conclusion: Tofacitinib demonstrated consistent safety up to 7.0 years. Data collected up to Month 36 support long‐term efficacy beyond the 52‐week maintenance study. Abstract :